PENINGKATAN KETERAMPILAN MENULIS MANUSKRIP JURNAL ILMIAH MENGGUNAKAN STRATEGI SYNERGETIC TEACHING PADA MAHASISWA PGSD UNNES - Nugraheti Sismulyasih Sb (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
27th January 2012 Higher Education General Directorates (ditjen dikti) Education ministry and Republic Of Indonesia culture publish form letter that comprising about scientific publication liabilities as requisite of pass programs master, magister, and doctor. Base of that verdict, researcher most draw for analyzes ability to make scientific journal manuscript PGSD UNNES'S college student, since new a portion PGSD'S college student little that understands with every consideration sistemation of scientific article writing. Researcher utilizes strategy Synergetic Teaching to increase ability writes scientific journal manuscript PGSD UNNES'S college student. Problem formula in observational it how to ability front end write scientific journal manuscript PGSD UNNES'S college student utilizes Synergetic Teaching? and If strategy Synergetic Teaching can increase ability writes scientific journal manuscript college student to the effect in this research is to increse writes skill college student write PGSD UNNES's journal manuscript year generation 2011. The method that is used in this research is method pseudo experiment attention by design one group pretest postest design .This observational that have been use 1) Essay and 2) nontest (questionnaire, observation / questionnaire, interview, and discussion). This research is executed on PGSD UNNES'S college student year generation 2011. This observational result is on reading ability early reference from 55% have been increase becomes 82,5% and understanding listen presentations of 47,5% have been increase as 72,5%. Meanwhile for one was complete through reading ability reference from 45% become down becomes 17,5% and understanding listen presentations of 52,5% as 27,5% that is mean by withstrategy Synergetic Teaching is effective for increase known ability of college student.